2020
DOI: 10.1038/s41416-020-0871-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of serial analysis of circulating tumour cells for detection of minimal residual disease of metastatic nasopharyngeal carcinoma

Abstract: Background Nasopharyngeal carcinoma (NPC) is an important cancer in Hong Kong. We aim to utilise liquid biopsies for serial monitoring of disseminated NPC in patients to compare with PET-CT imaging in detection of minimal residual disease. Method Prospective serial monitoring of liquid biopsies was performed for 21 metastatic patients. Circulating tumour cell (CTC) enrichment and characterisation was performed using a sized-based microfluidics CTC chip, enumerating by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The approach using a combination of different parameters has been proposed previously, such as the prognostic utility of integration of cfDNA with imaging-based response for early-stage EC [25]. Our earlier study in nasopharyngeal carcinoma (NPC) reported the clinical utility of integration of both EBV plasma DNA and CTC analysis for complementary enhancement of earlier detection of MRD in metastatic NPC patients with complete response by imaging [28]. To the best of our knowledge, there are no integration studies for serial monitoring of both the CTC enumeration and cfDNA level to examine its prognostic role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The approach using a combination of different parameters has been proposed previously, such as the prognostic utility of integration of cfDNA with imaging-based response for early-stage EC [25]. Our earlier study in nasopharyngeal carcinoma (NPC) reported the clinical utility of integration of both EBV plasma DNA and CTC analysis for complementary enhancement of earlier detection of MRD in metastatic NPC patients with complete response by imaging [28]. To the best of our knowledge, there are no integration studies for serial monitoring of both the CTC enumeration and cfDNA level to examine its prognostic role.…”
Section: Discussionmentioning
confidence: 99%
“…STRECK tubes were used for collection of 5 mL peripheral blood and processed within 72 h. The size-based CTC enrichment utilized CTChip ® FR1 microfluidic chips performed on a ClearCell ® FX1 System from Biolidics (Singapore) and immunofluorescence enumeration procedures were performed as previously described [28,40]. In brief, after red blood cell lysis, white blood cells (WBCs) were centrifuged at 500× g at room temperature for 10 min.…”
Section: Ctc Enrichment and Enumerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid biopsies have become standard procedures in the diagnosis and evaluation of many malignancies, making them powerful tools in diagnostics, evaluation of therapeutic efficiency, and minimal residual disease assessment [1,2]. The strong point of liquid biopsies is in their minimal invasiveness as compared to classical excisional biopsies, providing accessible means for real-time evaluation of the disease.…”
Section: Introductionmentioning
confidence: 99%